Frey’s procedure: short term follow up results in terms of pain, endocrine and exocrine status, a tertiary care centre experience - Sugumar, C.; Balakumaran, S.; Mundra, Mukund (International Journal of Research in Medical Sciences, 2020)
Background: Chronic pancreatitis, a debilitating disease which affects the patient to an extent to render him bedridden sometimes and often make him/her unable to perform daily work, leading to poor quality of life, severe emotional stress and financial burden. Frey’s procedure one of the most commonly performed surgery in patient of chronic pancreatitis with stones in pancreatic duct and small inflammatory head mass. This procedure had shown promising results in terms of pain control with unclear outcome with respect to exocrine and endocrine status. Methods: Study was conducted in Government Kilpauk Medical College, Chennai during March 2016 to December 2019. Total 21 patients were followed up for 18 months and Post-operative pain was analysed using pain scoring system used by Bloechle et al. Exocrine status in terms of diarrhea, bloating sensation and Fecal Elastase level(preoperative and postoperative) were analysed. Patient glycaemic status were also analysed and compared. Patient Nutritional status was analysed in terms of weight gain. Results: In this study there was significant improvement in pain after surgery in terms of VAS pain Score (Preop Mean-82.14, Post-op Mean- 9.76, p<0.001) , frequency of pain (Preop Mean-78.57, Post-op Mean- 14.29, p<0.001), analgesia required (Preop Mean-15, Post-op Mean- 3.10, p<0.001), and inability to work due to pain (Preop Mean-80.95, Post-op Mean- 11.90, p<0.001). Overall total Pain score was significantly improved after surgery (Preop Mean-256.67, Post-op Mean- 39.05, p<0.001). There was significant weight gain and significant improvement in Fecal Elastase level in patients following surgery, however there was no significant difference in pancreatic exocrine status on the basis of symptoms. Conclusions: Frey’s procedure is very effective in pain control in properly selected patients of chronic calcific pancreatitis, and it also improves nutritional status of patient. Frey’s procedure might improve patient exocrine and endocrine status but further multicentre studies are needed to come to a conclusion.